Epoxy resin for new energy automobile glue, epoxy resin composition and application
By using newly developed epoxy resin for new energy vehicle adhesives on aluminum automobile bodies, the problem of insufficient adhesion of traditional epoxy structural adhesives at low temperatures is solved, efficient bonding and impact resistance on aluminum automobile bodies is achieved, and the body life is extended.
Patent Information
- Application Number
- CN202411904240.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional epoxy structural adhesives are insufficient in the body of aluminum automobiles, especially after the hot and cold aging cycle, the adhesive force decreases at low temperatures, resulting in a shortening of the body life.
An epoxy resin for new energy vehicle glue was developed, and an etherification reaction with epoxy chloride was carried out through spirocyclic glycol and epoxy chloride, and a closed-loop reaction with sodium hydroxide. Combined with two batches of Lewis acid catalyst, an epoxy resin composition with a wide molecular weight distribution was prepared.
The epoxy resin composition exhibits high peeling adhesion at low temperatures, has excellent impact resistance and high toughness, and can maintain effective adhesion on aluminum automobile body and extend the body life.
Smart Images

Figure CN119708434A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of resin materials, and more specifically to an epoxy resin for new energy vehicle adhesive, an epoxy resin composition and applications. Background Art
[0002] With the development of new energy forms such as carbon emission, environmental protection and energy saving, new energy vehicles have rapidly replaced traditional fuel vehicles and achieved rapid development. A large number of new technologies such as body manufacturing have been continuously applied to achieve energy saving, lightweight, reliability, cost reduction and other goals, which have become the main sales goals of major automobile OEMs. Among them, replacing the steel frame body of traditional fuel vehicles with aluminum body has become the mainstream of new energy vehicles, especially aluminum integral body, reducing welding points, increasing the use of organic new materials, achieving body weight reduction, increasing the endurance of new energy batteries and other core technologies, which have become the key research direction of automobile OEMs.
[0003] Epoxy structural adhesive can adapt to the bonding requirements of different materials. The bonding process is relatively simple and can be completed quickly, which helps to improve production efficiency. In addition, the car body bonded by structural adhesive is more uniform in strength and stiffness and is not prone to deformation. Epoxy adhesive replaces traditional metal welding materials such as rivets, further reducing the weight of the car body and achieving the goals of lightweight, energy saving and high efficiency.
[0004] Traditional epoxy structural adhesives for metal car bodies have the characteristics of high strength and high adhesion. They can withstand large loads and maintain stable performance during long-term use. However, for aluminum car bodies, epoxy structural adhesives have insufficient adhesion, especially after hot and cold aging cycles, the adhesion decreases at low temperatures. Therefore, it is necessary to develop epoxy resin structural adhesives that have excellent adhesion to aluminum car bodies and still have effective adhesion after hot and cold aging, especially low-temperature adhesion, thereby increasing the life of the car body. Summary of the invention
[0005] In order to solve the above-mentioned problems, the present application provides an epoxy resin, an epoxy resin composition and an application for new energy vehicle adhesive. The epoxy resin composition has high peel adhesion at low temperature, excellent impact resistance and high toughness, which can meet the demand of aluminum automobile bodies in the automobile manufacturing industry for high-performance structural adhesives under low temperature conditions.
[0006] In the first aspect, the present application provides an epoxy resin for new energy vehicle adhesive, which adopts the following technical solution: An epoxy resin for new energy vehicle glue, which consists of component B1, component B2 and component B3 in GPC analysis, and the content of each component is as follows: Component B1 41.1-59.4% Component B2 27.7-35.8% Component B3 12.9-23.3%; The structural formula of the above-mentioned component B1 is as follows: The structural formula of the above-mentioned component B2 is as follows: The structural formula of above-mentioned component B3 is as follows: , where n=2-5.
[0007] In the second aspect, the present application provides a method for preparing an epoxy resin for new energy vehicle adhesive, which adopts the following technical scheme: The preparation method of the epoxy resin for new energy vehicle adhesive is as follows: after etherification reaction of spirocyclic glycol and epichlorohydrin by Lewis acid catalysis, the obtained etherification product A is subjected to ring-closing reaction with sodium hydroxide, and the reaction liquid obtained after the ring-closing reaction is successively subjected to refining reaction and post-treatment to obtain epoxy resin B. The preparation reaction process equation is as follows: The epoxy resin B is an epoxy resin for new energy vehicle glue. In GPC analysis, it is composed of component B1, component B2 and component B3. When n=0, it is component B1, when n=1, it is component B2; when n=2-5, it is component B3; the specific structural formula of component B1 is as follows: The structural formula of the above-mentioned component B2 is as follows: The structural formula of above-mentioned component B3 is as follows: Where n is 2-5.
[0008] Preferably, the Lewis acid used is BF3.Et2O, SnCl4 or AlCl3.
[0009] By adopting the above technical solution: BF3·Et2O, SnCl 4、 AlCl3 as a Lewis acid catalyst has good catalytic activity for the reaction of spirodiol and epichlorohydrin, and can improve the overall reaction efficiency.
[0010] The above-mentioned method for preparing epoxy resin for new energy vehicle adhesive comprises the following specific steps: S1, etherification reaction: spirocyclic glycol and toluene are added to a reaction vessel in sequence, the temperature is raised to 80-95°C, the pressure is -0.09MPa, reflux dehydration is carried out until the water content in the system is 0-0.05%, and reflux is stopped. At this time, nitrogen is filled into the system, and Lewis acid accounting for 80%-90% of the total Lewis acid is added under a nitrogen atmosphere, the stirring speed is controlled to be 150-200rpm, and the dropwise addition speed is controlled to be 0.85-1.04g / min under stirring conditions. Epichlorohydrin is uniformly added dropwise to the system, and after the dropwise addition is completed, the temperature is kept for 1.5-2.5h, and then the remaining Lewis acid is added, and the temperature is controlled to be 85-87°C for reaction for 1-2h to obtain reaction solution I; The amount of the spirodiol, toluene, Lewis acid catalyst and epichlorohydrin is such that the mass ratio of spirodiol: toluene: catalyst: epichlorohydrin is 1: 0.58: 0.001-0.0036: 0.67-0.82; S2, ring-closing reaction: adjust the pressure of the reaction solution I obtained after the etherification of S1 to -0.09 MPa and the temperature to 60-75°C, then control the dropping rate to 0.96-1.05 g / min to dropwise add a 48.5% mass percentage concentration of NaOH aqueous solution, keep warm for 2-5 hours after the dropwise addition is completed, reflux dehydration during the dropwise addition, and then introduce nitrogen to restore the pressure from negative pressure to normal pressure to obtain a reaction solution II; The amount of the NaOH aqueous solution having a mass percentage concentration of 48.5% is calculated in molar ratio relative to the spirodiol used to prepare the reaction solution I, and the molar ratio of spirodiol to the sodium hydroxide in the NaOH aqueous solution having a mass percentage concentration of 48.5% is 1:2.1-2.3; S3, refining reaction: the reaction solution II obtained after the ring-closing reaction of S2 is placed under an inert gas atmosphere, the temperature is controlled at 75-85° C., a phase transfer catalyst and a 32% by mass concentration NaOH aqueous solution are added in sequence, and a refining reaction is carried out for 2-4 hours to obtain a crude product; The phase transfer catalyst may be benzyltriethylammonium chloride (TEBAC), tetramethylammonium chloride or polyethylene glycol; S4, post-treatment: add 0.8-1.2 times the volume of the crude product of distilled water to dissolve the lower layer of sodium chloride in the crude product in S3, remove the aqueous phase by standing phase separation, and then wash 3 times with distilled water. During the second washing process, phosphoric acid is used to neutralize the residual sodium hydroxide, and the pH value of the system is adjusted to 7. After the third washing, filter with 500 mesh diatomaceous earth, and the obtained filtrate is controlled at a pressure of -0.09 MPa and a temperature of 120 ° C. After the solvent is removed by reduced pressure distillation, an epoxy resin for new energy vehicle glue is obtained.
[0011] By adopting the above technical solution: the two-batch addition of the Lewis acid catalyst is conducive to controlling the reaction rate, so that the molecular weight distribution of the product is effectively adjusted.
[0012] Preferably, in step S3, the phase transfer catalyst and the 32% by mass concentration NaOH aqueous solution are in a mass ratio of 1:0.087:0.0006 of spirodiol: 32% by mass concentration NaOH aqueous solution: phase transfer catalyst relative to the spirodiol used in the preparation of the reaction solution I.
[0013] By adopting the above technical solution: the synergistic effect of various reaction conditions is optimized, and the reaction rate and product distribution can be effectively balanced.
[0014] In a third aspect, the present application provides an epoxy resin composition, which adopts the following technical solution: An epoxy resin composition containing epoxy resin for new energy vehicle adhesive, wherein the raw materials used for its preparation include the above-mentioned epoxy resin for new energy vehicle adhesive, and also include 4,8-tricyclo[5.2.1.O(2,6)]decanedimethanol diglycidyl ether epoxy resin, a blocked toughening agent, a curing agent and an accelerator; The above-mentioned epoxy resin composition containing epoxy resin for new energy vehicle glue, the raw material composition and amount used in its preparation are calculated by mass as follows: The closed toughening agent is Lepro FM 9504, Lepro FM 9506, Lepro FM 9508, DY965 or QR-9466 produced by Complex High-tech Materials (Shanghai) Co., Ltd. The curing agent is a dicyandiamide curing agent, and the dicyandiamide curing agent is dicyandiamide; The accelerator is an organic urea accelerator, and the organic urea accelerator is UR 500.
[0015] The various raw material components in the above-mentioned epoxy resin composition containing epoxy resin for new energy vehicle adhesive should be stored separately and mixed when used.
[0016] Preferably, the raw material composition and amount used in the preparation of the above-mentioned epoxy resin composition containing epoxy resin for new energy vehicle glue are calculated as follows by mass fraction:
[0017] By adopting the above technical scheme: the epoxy resin composition containing epoxy resin for new energy vehicle adhesive has significantly improved weather resistance, bending strength, impact strength and peel strength after bonding compared with the epoxy resin composition not containing epoxy resin for new energy vehicle adhesive.
[0018] The reasons may be: During the etherification reaction in the preparation process of epoxy resin for new energy vehicle glue, the molecular weight distribution of the etherification product is improved by adding Lewis acid catalyst in batches, thereby changing the molecular weight distribution of the components of the epoxy resin for new energy vehicle glue, thereby significantly improving the bonding performance of the epoxy resin composition containing the epoxy resin for new energy vehicle glue.
[0019] 4,8-tricyclo[5.2.1.0(2,6)]decanedimethanol diglycidyl ether epoxy resin, whose unique molecular structure gives it excellent toughness and strength, can synergistically improve the toughness of the entire resin system when mixed with epoxy resin for new energy vehicle adhesive and blocked toughening agent, thereby enhancing the impact resistance of the epoxy resin composition containing epoxy resin for new energy vehicle adhesive; The blocked toughening agent is used as a toughening agent, which has a blocked isocyanate structure and a relatively long flexible polyol ether chain, wherein the blocked isocyanate structure is unblocked during the curing process of the epoxy resin composition, and a certain chemical bond of a carbamate structure can be formed on the surface of the aluminum substrate, thereby enhancing the adhesion of the aluminum substrate; wherein the relatively long flexible polyol ether chain can further enhance the flexibility of the epoxy resin composition, and still maintain its flexibility at low temperatures, thereby enhancing the toughness of the composition containing the epoxy resin for new energy vehicle adhesive at low temperatures; In particular, when the blocked toughening agent is used together with the epoxy resin for new energy vehicle adhesive and 4,8-tricyclo[5.2.1.0(2,6)]decanedimethanol diglycidyl ether epoxy resin, the synergistic effect between the three can greatly improve the peel strength of the epoxy resin composition after application.
[0020] The preparation method of the above-mentioned epoxy resin composition containing epoxy resin for new energy vehicle glue comprises the following steps: adding epoxy resin for new energy vehicle glue, 4,8-tricyclo[5.2.1.O(2,6)]decanedimethanol diglycidyl ether epoxy resin, blocked toughening agent, curing agent and accelerator in a container in sequence, and then controlling the rotation speed to 2000-3000rpm for homogeneous mixing to obtain an epoxy resin composition containing epoxy resin for new energy vehicle glue.
[0021] The above-mentioned epoxy resin composition containing epoxy resin for new energy automobile adhesive is used as aluminum automobile body structural adhesive, and the specific use method is as follows: An epoxy resin composition containing epoxy resin for new energy vehicle adhesive is prepared according to the above-mentioned preparation method of the epoxy resin composition containing epoxy resin for new energy vehicle adhesive; When used as aluminum automobile body structural adhesive, the coating thickness of the epoxy resin composition is controlled to be 0.30-0.40 mm. After coating, the temperature is sequentially controlled to be 110° C. for curing for 1 hour and 150° C. for curing for 1 hour.
[0022] Beneficial technical effects of this application: The epoxy resin for new energy vehicle adhesive of the present application uses Lewis acid as a catalyst to catalyze the reaction of spirodiol and epichlorohydrin, and controls the addition of the catalyst in two batches, thereby finally obtaining an epoxy resin for new energy vehicle adhesive with a wide molecular weight distribution; Furthermore, the epoxy resin composition containing epoxy resin for new energy vehicle adhesive of the present application has high impact strength, tensile strength, peel strength, good resistance to temperature change, and still maintains good bonding performance under low temperature conditions, due to the synergistic effect between the epoxy resin for new energy vehicle adhesive with a wide molecular weight distribution and 4,8-tricyclo[5.2.1.O(2,6)]decanedimethanol diglycidyl ether epoxy resin and a blocked toughening agent. The epoxy resin composition containing epoxy resin for new energy vehicle adhesive has good resistance to temperature change, and can be used for aluminum body vehicle structural adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the GPC elution curve of the product prepared in Example 1; Figure 2 This is a table showing the GPC molecular weight statistics of the product prepared in Example 1. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with the examples. Except for the special instructions below, the raw materials used in the present application are all common commercially available materials.
[0025] Performance testing Determination method of epoxy equivalent value: GB / T 4612-2008, instrument model: METTLER TOLEDO, using hydrogen bromide generated by 0.1 mol / L perchloric acid and tetraethylammonium bromide as the ring-opening agent of epoxy group, and then determining the endpoint by potentiometric titration to obtain the epoxy equivalent value; Tests of tensile properties (tensile strength), shear properties (shear strength), and impact resistance (impact strength): According to GB / T 2567-2008 "Test Method for Properties of Resin Castings", the epoxy resin compositions containing epoxy resin for new energy vehicle adhesive prepared in the examples and comparative examples of this application were prepared into aluminum-based test specimens, and the tensile strength, shear strength and impact strength were tested respectively; In the above-prepared test specimens, the coating thickness of the epoxy resin composition containing epoxy resin for new energy vehicle adhesive is 0.35 mm. After coating, the temperature is controlled to be cured at 110° C. for 1 hour and 150° C. for 1 hour.
[0026] Temperature resistance test: The peel strength of the aluminum-based T-type test strip was tested at 80°C and -40°C respectively; Aging performance test: Aging method: The aging test chamber conditions were set to 85°C and 85% relative humidity, and the aluminum-based T-type test specimens were placed in the aging test chamber for 1000 hours of aging; The -40℃ T-type peel strength of the aluminum-based T-type test strips was tested before aging and after aging for 1000 hours at -40℃, and the peel strength attenuation percentage was calculated. The calculation formula for the peel strength attenuation percentage is: (AB) / A*100%, where A is the peel strength of the aluminum-based T-type test strip at -40°C, and B is the peel strength of the aluminum-based T-type test strip at -40°C after aging for 1000 hours.
[0027] GPC test method: characterized by gel permeation chromatography (GPC), according to GB / T 27843-2011, the name of the instrument used for the measurement is Waters high performance liquid chromatography, model Waters 1515.
[0028] Example 1 An epoxy resin composition containing epoxy resin for new energy vehicle adhesive, the composition and amount of each raw material used in its preparation are shown in Table 1 below: Table 1. Composition and dosage of each raw material of the epoxy resin composition of Example 1 The above-mentioned new energy automobile glue epoxy resin is prepared by the following method: S1, etherification reaction: 304g of spirocyclic glycol and 178g of toluene were added to a 1L four-necked flask, the temperature was raised to 88°C, and refluxed for dehydration under a pressure of -0.09MPa until the water content in the reaction system was 0.03%, then the reflux was stopped, and nitrogen was filled into the system for protection, 0.44g (80% of the total amount of BF3·Et2O) of BF3·Et2O was first added, and after stirring for 5min, 250.2g of epichlorohydrin was added, and the dripping rate of epichlorohydrin was controlled to be 1.04g / min. After keeping warm for 2h, 0.11g of BF3·Et2O remained, and the reaction was stopped after 1h to obtain reaction solution I; The mass ratio of spirodiol: toluene: BF3·Et2O: epichlorohydrin is 1: 0.58: 0.0018: 0.82; S2, ring-closing reaction: the negative pressure of the reaction system after etherification of S1 was adjusted to -0.09 MPa, the reaction temperature was adjusted to 75°C, 189.7 g of a 48.5% by mass NaOH aqueous solution was added dropwise to the reaction system at a rate of 1.05 g / min, and the temperature was kept for 2 h after the addition was completed; During the above process of adding the NaOH aqueous solution dropwise and keeping warm, reflux and dehydrate; After the above insulation is completed, nitrogen is introduced to restore the pressure from negative pressure to normal pressure to obtain reaction solution II; In the above ring-closing reaction, the amount of the NaOH aqueous solution with a mass percentage concentration of 48.5% is calculated by molar ratio, and the molar ratio of the spirodiol used in the reaction solution I prepared by the etherification reaction in step S1 to the sodium hydroxide in the NaOH aqueous solution with a mass percentage concentration of 48.5% is 1:2.3; S3, refining reaction: nitrogen was charged into the reaction solution II after the ring-closing reaction in S2 for protection, the system temperature was controlled to 80°C, and then 0.18g of phase transfer catalyst TEBAC and 26.3g of a 32% by mass concentration of NaOH aqueous solution were added in sequence, and the refining reaction was carried out for 2h to obtain a crude product; S4, post-treatment: the crude product obtained in S3 was added to 300mL of distilled water to dissolve the lower salt foot, and the aqueous phase was removed by standing phase separation. The washing process was repeated 3 times. During the second washing process, phosphoric acid was used to neutralize the residual sodium hydroxide, and the pH value of the system was adjusted to 7. The product after washing was filtered with a diatomaceous earth filter to remove mechanical impurities such as aging resin. The filtrate obtained after filtration was controlled at a pressure of -0.098MPa and a temperature of 120°C for decompression distillation to remove the solvent, and an epoxy resin for new energy vehicle glue was obtained; GPC was used to analyze the epoxy resin for new energy vehicle adhesive at a column temperature of 40°C with tetrahydrofuran as the mobile phase. The GPC elution curve is shown in the figure below: Figure 1 As shown, from Figure 1 It can be seen that there are three peaks, which shows that the epoxy resin for new energy vehicle glue contains three components, represented by component B1, component B2 and component B3 respectively; the GPC molecular weight statistical results are shown in the table below Figure 2 As shown, through Figure 2 It can be seen that the mass percentages of component B1, component B2 and component B3 of epoxy resin for new energy vehicle adhesive are shown in Table 2 below: Table 2. Composition, content and epoxy equivalent value of epoxy resin composition for new energy vehicle adhesive The above-mentioned method for preparing an epoxy resin composition containing epoxy resin for new energy vehicle glue comprises the following specific steps: adding epoxy resin for new energy vehicle glue, 4,8-tricyclo[5.2.1.O(2,6)]decanedimethanol diglycidyl ether epoxy resin, closed toughening agent, curing agent and accelerator into a high-speed shear homogenizer in sequence, controlling the speed to 2500rpm for high-speed shear homogenization, discharging the material after homogenization, and obtaining an epoxy resin composition containing epoxy resin for new energy vehicle glue.
[0029] Comparative Example 1 of Example 1 An epoxy resin composition containing NPEL-128 epoxy resin, i.e., an epoxy resin composition not containing epoxy resin for new energy vehicle adhesive. The raw material components and amounts used in its preparation are the same as those in Example 1, except that the epoxy resin for new energy vehicle adhesive is replaced by NPEL-128 (EEW=186 g / eq) resin in an equal amount.
[0030] The above-mentioned epoxy resin composition containing NPEL-128 epoxy resin, that is, the preparation method of the epoxy resin composition that does not contain epoxy resin for new energy vehicle glue, is to add NPEL-128 (EEW=186g / eq) resin, 4,8-tricyclo[5.2.1.O(2,6)]decanedimethanol diglycidyl ether epoxy resin, blocked toughening agent, curing agent, and accelerator into a high-speed shear homogenizer in sequence, control the speed to 2500rpm for high-speed shear homogenization, and discharge the material after homogenization to obtain the epoxy resin composition containing NPEL-128 epoxy resin, that is, the epoxy resin that does not contain epoxy resin for new energy vehicle glue.
[0031] The aging properties of the epoxy resin composition containing the epoxy resin for new energy vehicle glue obtained in Example 1 and the epoxy resin composition containing the NPEL-128 epoxy resin obtained in Comparative Example 1 of Example 1 were tested respectively, and the peel strength at -40°C (peel strength before aging) and the peel strength at -40°C after aging for 1000h (peel strength after aging) were calculated, and the attenuation percentage of the peel strength was calculated. The results are shown in Table 3 below: Table 3. Peel strength and peel strength attenuation percentage of epoxy resin compositions before and after aging It can be seen from Table 3 above that the epoxy resin composition containing epoxy resin for new energy vehicle adhesive obtained in Example 1 is compared with the epoxy resin composition containing NPEL-128 epoxy resin of Comparative Example 1 of Example 1, that is, the epoxy resin composition not containing epoxy resin for new energy vehicle adhesive. The peel strength before and after aging is increased by about 46.9% and 62.9%, respectively, and the peel strength attenuation percentage is reduced by 9.3%, which shows that the epoxy resin composition containing epoxy resin for new energy vehicle adhesive of the present application has better anti-aging effect and better stability at low temperature.
[0032] Comparative Example 2 of Example 1 An epoxy resin composition containing epoxy resin for new energy vehicle glue, wherein the raw material components and amounts used in its preparation are the same as those in Example 1, but the raw material epoxy resin for new energy vehicle glue is prepared by the following preparation method: S1, etherification: replace BF3·Et2O with an equal molar amount of liquid caustic soda, and the rest is the same as step S1 in Example 1 to obtain reaction solution I; S2, ring-closing reaction: same as step S2 in Example 1; S3, refining: same as step S3 in Example 1; S4, post-processing: the same as step S4 in Example 1, to obtain epoxy resin for new energy vehicle glue.
[0033] The preparation method of the above-mentioned epoxy resin composition containing epoxy resin for new energy vehicle adhesive is the same as that in Example 1.
[0034] The composition of the epoxy resin for new energy vehicle glue obtained in Example 1 and Comparative Example 2 of Example 1 and the epoxy equivalent value of the epoxy resin composition containing the epoxy resin for new energy vehicle glue finally obtained were measured, and the measurement results are shown in Table 4 below: Table 4: Composition, content and epoxy equivalent value of epoxy resin composition for new energy vehicle adhesive The tensile strength, shear strength, impact strength and T-peel strength of the epoxy resin composition containing epoxy resin for new energy vehicle adhesive prepared in Example 1 and Comparative Example 2 of Example 1 were measured respectively at 80° C. and -40° C., and the results are shown in Table 5 below: Table 5: Tensile, shear, impact strength, and T-peel strength at 80°C and -40°C of epoxy resin compositions The raw material used in the epoxy resin composition containing epoxy resin for new energy vehicle glue of the above-mentioned embodiment 1 is the epoxy resin for new energy vehicle glue. The raw material used in the epoxy resin composition containing epoxy resin for new energy vehicle glue of the comparative example 2 of embodiment 1 is the epoxy resin for new energy vehicle glue. The epoxy resin composition containing epoxy resin for new energy vehicle glue is prepared using liquid alkali as a catalyst. Combining the above Tables 5 and 6, it can be seen that the epoxy resin composition containing epoxy resin for new energy vehicle glue obtained in embodiment 1 has a tensile strength, shear strength, impact strength and T-peel strength at 80°C and -40°C, respectively, compared with the epoxy resin composition containing epoxy resin for new energy vehicle glue obtained in comparative example 2 of embodiment 1. The epoxy resin composition is improved by 4.3%, 15.5%, 82.2%, 26.0%, and 59.3%, respectively. The possible reason is that the use of Lewis acid BF3·Et20 as a catalyst for the etherification reaction changed the distribution of the components of the epoxy resin for new energy vehicle adhesive. The content of component B1 was significantly reduced, and the contents of components B2 and B3 were significantly increased. The content of component B2 increased by 1.14 times and the content of B3 increased by 8.06 times.
[0035] The above results show that when the raw material epoxy resin for new energy vehicle adhesive used in the epoxy resin composition containing epoxy resin for new energy vehicle adhesive uses Lewis acid BF3·Et20 as a catalyst in the preparation process, the epoxy resin composition containing epoxy resin for new energy vehicle adhesive finally obtained has good tensile properties, shear properties, impact resistance, adhesion properties at low temperatures, and temperature change resistance.
[0036] Example 2 An epoxy resin composition containing epoxy resin for new energy vehicle glue, wherein the composition and amount of each raw material used in its preparation are the same as those in Example 1, but the raw material epoxy resin for new energy vehicle glue is prepared by the following preparation method: S1, etherification: add 304g spirocyclic glycol and 178g toluene to a 1L four-necked flask, heat to 88°C, reflux and dehydrate under -0.09MPa until the water content in the reaction system is 0.03% and then stop refluxing, then fill the system with nitrogen for protection, add 0.55g BF3·Et2O, stir for 5min, add 250.2g epichlorohydrin, control the dripping rate of epichlorohydrin to 1.04 g / min, keep the reaction for 3h, and then stop; S2, ring-closing reaction: same as step S2 in Example 1; S3, refining: same as step S3 in Example 1; S4, post-processing: the same as step S4 in Example 1, to obtain epoxy resin for new energy vehicle glue.
[0037] The preparation method of the above-mentioned epoxy resin composition containing epoxy resin for new energy vehicle adhesive is the same as that in Example 1.
[0038] Embodiment 3-4 An epoxy resin composition containing epoxy resin for new energy vehicle glue, wherein the composition and amount of each raw material used in its preparation are the same as those in Example 1, but the raw material epoxy resin for new energy vehicle glue is prepared by the following preparation method: S1, etherification: AlCl3 and SnCl4 are used to replace BF3·Et2O in equal amounts, and the other steps are the same as those in S1 of Example 1 to obtain reaction solution I; S2, ring-closing reaction: same as step S2 in Example 1; S3, refining: same as step S3 in Example 1; S4, post-processing: same as step S4 in Example 1; The preparation method of the above-mentioned epoxy resin composition containing epoxy resin for new energy vehicle adhesive is the same as that in Example 1.
[0039] The composition of the epoxy resin for new energy vehicle adhesive and the epoxy equivalent value of the epoxy resin composition containing the epoxy resin for new energy vehicle adhesive in Examples 2-4 were measured and compared with Example 1. The results are shown in Table 6 below; Table 6: Composition, content and epoxy equivalent value of epoxy resin composition for new energy vehicle adhesive The epoxy equivalent of the epoxy resin composition containing epoxy resin for new energy vehicle adhesive obtained in Examples 1-4 of Table 5 is 248-257 g / eq, which meets the performance requirements when used as automotive structural adhesive.
[0040] The tensile strength, shear strength, impact strength and T-peel strength of the epoxy resin composition containing epoxy resin for new energy vehicle adhesive of Examples 2-4 at 80° C. and -40° C. were measured and compared with those of Example 1. The results are shown in Table 7 below; Table 7: Tensile, shear, impact strength, and T-peel strength at 80°C and -40°C of epoxy resin compositions From the combined analysis of Tables 6 and 7 above, it can be seen that when Lewis acid BF3·Et20, AlCl3, and SnCl4 are used as catalysts in the preparation process of epoxy resin for new energy vehicle glue, the content distribution of the components of the epoxy resin for new energy vehicle glue is changed, and the epoxy resin composition containing the epoxy resin for new energy vehicle glue finally obtained has good tensile properties, shear properties, impact resistance, low temperature bonding properties, and temperature change resistance.
[0041] Further, the epoxy resin composition containing epoxy resin for new energy vehicle glue obtained in Example 1 has a tensile strength, shear strength, impact strength and T-peel strength at 80°C and -40°C respectively increased by 9.4%, 12.4%, 6.0%, 31.8% and 13.3% compared to the epoxy resin composition containing epoxy resin for new energy vehicle glue obtained in Example 2. This shows that in the preparation process of epoxy resin for new energy vehicle glue, when Lewis acid BF3·Et20 (Example 1) is added in two batches for catalytic etherification reaction, compared with adding Lewis acid BF3·Et20 (Example 2) once for catalytic etherification reaction, the epoxy resin composition containing epoxy resin for new energy vehicle glue finally obtained has better tensile properties, shear properties, impact resistance, low temperature bonding properties, and temperature change resistance.
[0042] Furthermore, the epoxy resin composition containing epoxy resin for new energy vehicle adhesive obtained in Example 1 has improved tensile strength, shear strength, impact strength and T-peel strength at 80°C and -40°C compared with the epoxy resin composition containing epoxy resin for new energy vehicle adhesive obtained in Examples 3 and 4. This indicates that it is more preferable to use Lewis acid BF3·Et20 (BF3·Et20 is used in Example 1, and AlCl3 and SnCl4 are used in Examples 3 and 4, respectively) to catalyze the etherification reaction in the preparation process of epoxy resin for new energy vehicle adhesive.
[0043] Example 5 An epoxy resin composition containing epoxy resin for new energy vehicle glue, wherein the composition and amount of each raw material used in its preparation are the same as those in Example 1, but the raw material epoxy resin for new energy vehicle glue is prepared by the following preparation method: S1, etherification: 304g of spirocyclic glycol and 178g of toluene were added to a 1L four-necked flask, the temperature was raised to 88°C, and refluxed for dehydration under a pressure of -0.09MPa until the water content in the reaction system was 0.03%, then the reflux was stopped, and nitrogen was filled into the system for protection, 0.2432g (80% of the total amount of BF3·Et2O) of BF3·Et2O was added first, and after stirring for 5min, 250.2g of epichlorohydrin was added, and the dripping rate of epichlorohydrin was controlled to be 1.04g / min. After keeping warm for 2h, 0.0608g of BF3·Et2O remained, and the reaction was stopped after 1h to obtain reaction solution I; The mass ratio of spirodiol: toluene: BF3·Et2O: epichlorohydrin is 1: 0.58: 0.0010: 0.82; S2, ring-closing reaction: same as step S2 in Example 1; S3, refining: same as step S3 in Example 1; S4, post-processing: same as step S4 in Example 1; The preparation method of the above-mentioned epoxy resin composition containing epoxy resin for new energy vehicle adhesive is the same as that in Example 1.
[0044] Example 6 An epoxy resin composition containing epoxy resin for new energy vehicle glue, wherein the raw material components and amounts used in its preparation are the same as those in Example 1, but the raw material epoxy resin for new energy vehicle glue is prepared by the following preparation method: S1, etherification: 304g of spirocyclic glycol and 178g of toluene were added to a 1L four-necked flask, the temperature was raised to 88°C, and refluxed for dehydration under a pressure of -0.09MPa until the water content in the reaction system was 0.03%, then the reflux was stopped, and nitrogen was filled into the system for protection, 0.876g (80% of the total amount of BF3·Et2O) of BF3·Et2O was added first, and after stirring for 5min, 250.2g of epichlorohydrin was added, and the dripping rate of epichlorohydrin was controlled to be 1.04g / min. After keeping warm for 2h, 0.219g of BF3·Et2O remained, and the reaction was stopped after 1h to obtain reaction solution I; The mass ratio of spirodiol: toluene: BF3·Et2O: epichlorohydrin is 1: 0.58: 0.0036: 0.82; S2, ring-closing reaction: same as step S2 in Example 1; S3, refining: same as step S3 in Example 1; S4, post-processing: same as step S4 in Example 1; The preparation method of the above-mentioned epoxy resin composition containing epoxy resin for new energy vehicle adhesive is the same as that in Example 1.
[0045] The composition of the epoxy resin for new energy vehicle adhesive and the epoxy equivalent value of the epoxy resin composition containing the epoxy resin for new energy vehicle adhesive in Examples 5-6 were measured and compared with Example 1. The results are shown in Table 8 below; Table 8: Composition of epoxy resin for new energy vehicle adhesive and epoxy equivalent value of epoxy resin composition The tensile strength, shear strength, impact strength and T-peel strength of the epoxy resin composition containing epoxy resin for new energy vehicle adhesive obtained in Examples 5-6 at 80° C. and -40° C. were measured. The test results are shown in Table 9 below: Table 9: Tensile, shear, impact strength, and T-peel strength at 80°C and -40°C of epoxy resin compositions Combining the analysis of Table 8 and Table 9 above, it can be seen that BF3·E is used in the preparation of epoxy resin for new energy vehicle glue. t2 When O is a catalyst, the content distribution of the components of the epoxy resin for new energy vehicle glue is changed, and the finally obtained epoxy resin composition containing the epoxy resin for new energy vehicle glue has better tensile properties, shear properties, impact resistance, adhesion properties at low temperatures, and resistance to temperature changes.
[0046] Further, Example 1 (Spirocyclic glycol in the preparation process of epoxy resin for new energy vehicle adhesive: catalyst BF3·E t2 The epoxy resin composition containing epoxy resin for new energy vehicle glue obtained in Example 5 (the weight ratio of spiroglycol: catalyst BF3·Et2O in the preparation process of epoxy resin for new energy vehicle glue is 1:0.0018) has an epoxy resin composition containing epoxy resin for new energy vehicle glue that is increased by 1.8%, 2.5%, 4.0%, 16% and 9.8% in tensile strength, shear strength, impact strength and T-peel strength at 80°C and -40°C, respectively, compared with Example 6 (the weight ratio of spiroglycol: catalyst BF3·Et2O in the preparation process of epoxy resin for new energy vehicle glue is 1:0.0036), and an epoxy resin composition containing epoxy resin for new energy vehicle glue that is increased by 0.9%, 1.4%, 2.4%, 3.6% and 2% in tensile strength, shear strength, impact strength and T-peel strength at 80°C and -40°C, respectively.
[0047] The above results show that the preferred weight ratio of spirocyclic glycol and catalyst BF3·Et2O in the preparation process of epoxy resin for new energy vehicle glue of the present application is 1:0.0018.
[0048] Example 7 An epoxy resin composition containing epoxy resin for new energy vehicle glue, wherein the composition and amount of each raw material used in its preparation are the same as those in Example 1, but the raw material epoxy resin for new energy vehicle glue is prepared by the following preparation method: S1, etherification: first add 0.275g of BF3.Et2O, stir for 5min, then add 250.2g of epichlorohydrin, control the dripping rate of epichlorohydrin to 1.04g / min, keep warm for 2h, and then 0.275g of BF3.Et2O remains, and the reaction is stopped after 1h, that is, the input ratio of the catalyst BF3.Et2O is different between the two batches, and the feeding ratio is the first batch: the second batch = 50%: 50% according to mass percentage, and the rest is the same as step S1 in Example 1, to obtain reaction solution I; S2, ring-closing reaction: same as step S2 in Example 1; S3, refining: same as step S3 in Example 1; S4, post-processing: same as step S4 in Example 1; The preparation method of the above-mentioned epoxy resin composition containing epoxy resin for new energy vehicle adhesive is the same as that in Example 1.
[0049] Example 8 An epoxy resin composition containing epoxy resin for new energy vehicle glue, wherein the composition and amount of each raw material used in its preparation are the same as those in Example 1, but the raw material epoxy resin for new energy vehicle glue is prepared by the following preparation method: S1, etherification: first add 0.33g of BF3.Et2O, stir for 5min, then add 250.2g of epichlorohydrin, control the dripping rate of epichlorohydrin to 1.04g / min, keep warm for 2h, and then 0.22g of BF3.Et2O remains. The reaction is stopped after 1h, that is, the input ratio of the catalyst BF3.Et2O is different between the two batches, and the feeding ratio is the first batch: the second batch = 60%: 40% by mass percentage, and the rest is the same as step S1 in Example 1, to obtain reaction solution I; S2, ring-closing reaction: same as step S2 in Example 1; S3, refining: same as step S3 in Example 1; S4, post-processing: same as step S4 in Example 1; The preparation method of the above-mentioned epoxy resin composition containing epoxy resin for new energy vehicle adhesive is the same as that in Example 1.
[0050] The composition of the epoxy resin for new energy vehicle adhesive and the epoxy equivalent value of the epoxy resin composition containing the epoxy resin for new energy vehicle adhesive in Examples 7-8 were measured and compared with Example 1. The results are shown in Table 10 below; Table 10: Composition, content and epoxy equivalent value of epoxy resin composition for new energy vehicle adhesive The tensile strength, shear strength, impact strength and T-peel strength of the epoxy resin compositions containing epoxy resin for new energy vehicle adhesive of Examples 1, 7-8 and at 80°C and -40°C were measured, and the results are shown in Table 11 below: Table 11: Tensile, shear, impact strength, and T-peel strength at 80°C and -40°C of epoxy resin compositions It can be seen from Tables 10 and 11 that BF3·E is used in the preparation of epoxy resin for new energy vehicle adhesive. t2 When O is the catalyst, the feeding ratios of the two batches of the catalyst BF3·Et2O are 80%:20%, 60%:40%, and 50%:50% respectively, which changes the content distribution of the components of the epoxy resin for new energy vehicle adhesive. The epoxy resin composition containing the epoxy resin for new energy vehicle adhesive finally obtained has good tensile properties, shear properties, impact resistance, low temperature bonding properties, and temperature change resistance.
[0051] Furthermore, the epoxy resin composition containing epoxy resin for new energy vehicle glue obtained in Example 1 is 2.6%, 6.0%, 10.5%, 26.1%, and 8.5% higher in tensile strength, shear strength, impact strength, and T-peel strength at 80°C and -40°C than the epoxy resin composition containing epoxy resin for new energy vehicle glue obtained in Example 7, respectively. The tensile, shear, and impact strength of the epoxy resin composition sample containing epoxy resin for new energy vehicle glue obtained in Example 8, as well as the T-peel strength at 80°C and -40°C, are increased by 2.2%, 3.0%, 4.5%, 11.5%, and 8.5%, respectively. This indicates that when the two batches of the particularly preferred catalyst BF3·Et2O are fed at a ratio of 80%:20%, the epoxy resin composition containing epoxy resin for new energy vehicle glue finally obtained has better tensile properties, shear properties, impact resistance, adhesion properties at low temperatures, and temperature variation resistance.
[0052] Examples 9-15 An epoxy resin composition containing epoxy resin for new energy vehicle adhesive, the raw materials used in its preparation are the same as those in Example 1, and the specific amount of each raw material is shown in Table 12 below: Table 12: Composition and dosage of raw materials of epoxy resin compositions of Examples 1, 9-15
[0053] The preparation method of the epoxy resin composition containing epoxy resin for new energy vehicle adhesive is the same as that of Example 1.
[0054] The tensile strength, shear strength, impact strength and T-peel strength of the epoxy resin compositions containing epoxy resin for new energy vehicle adhesive obtained in Examples 9-15 at 80°C and -40°C were measured and compared with those in Example 1. The results are shown in Table 13 below: Table 13: Tensile strength, shear strength, impact strength, and T-peel strength at 80°C and -40°C of epoxy resin compositions The peel strength of the epoxy resin composition containing the epoxy resin for new energy vehicle adhesive obtained in Examples 9-15 at -40°C (peel strength before aging) and the peel strength at -40°C after aging for 1000h (peel strength after aging) were calculated, and compared with Example 1. The results are shown in Table 14 below: Table 14. Peel strength and peel strength attenuation percentage of epoxy resin compositions before and after aging It can be seen from Tables 13 and 14 above that the epoxy resin compositions containing epoxy resin for new energy vehicle glue obtained in Examples 1 and 9-15 all have good tensile properties, shear properties, impact resistance, low temperature bonding properties, temperature variation resistance and aging properties, and in the peel strength test before and after high and low temperature aging, the -40°C T-type peel strength attenuation percentage before and after aging is only 11.9% at most. In particular, the epoxy resin compositions containing epoxy resin for new energy vehicle glue obtained in Example 1 all have better tensile properties, shear properties, impact resistance, low temperature bonding properties, temperature variation resistance, and in the peel strength test after high and low temperature aging, the -40°C T-type peel strength attenuation percentage before and after aging is only 6.3%.
[0055] In summary, the epoxy resin for new energy vehicle glue of the present application adopts the addition of Lewis acid as a catalyst in two batches during the preparation process, wherein the dosage ratio of spirodiol and Lewis acid catalyst is 1:0.001-0.0036, and the proportion of catalyst added in the first batch is 80%-90%. The obtained epoxy resin for new energy vehicle glue is composed of component B1, component B2 and component B3 after GPC analysis, wherein component B1 is 41.1-59.4%, component B2 is 27.7-35.8%, and component B3 is 12.9-23.3%.
[0056] In particular, while ensuring the proportion of component B1, the proportions of components B2 and B3 are increased to make them have a wider molecular weight distribution. The epoxy resin composition containing epoxy resin for new energy vehicle adhesive prepared by using the epoxy resin for new energy vehicle adhesive as one of the raw materials has good tensile properties, shear properties, impact resistance, adhesion properties at low temperatures, resistance to temperature change, etc., and therefore can be used for aluminum body automotive structural adhesives.
[0057] The above are all modifications without creative contribution or solutions that obviously constitute technical inspiration that can be made to the present embodiment as needed by technical personnel in this field after reading this specification, but they should be protected by patent law as long as they are within the scope of the claims of this application.
Claims
1. An epoxy resin for new energy vehicle adhesive, characterized in that: The epoxy resin for new energy vehicle glue GPC analysis is composed of component B1, component B2 and component B3, and the mass percentage of each component is as follows: Component B1 41.1-59.4% Component B2 27.7-35.8% Component B3 12.9-23.3%; The structural formula of component B1 is as follows: The structural formula of the above-mentioned component B2 is as follows: The structural formula of above-mentioned component B3 is as follows: , Where n is 2-5.
2. The method for preparing epoxy resin for new energy vehicle glue according to claim 1, Features Here are the steps: First, spirodiol and epichlorohydrin were subjected to etherification reaction catalyzed by Lewis acid; Then, the etherification product obtained by the etherification reaction is subjected to a ring-closing reaction with sodium hydroxide; Finally, the reaction liquid obtained after the ring-closing reaction is subjected to a refining reaction and post-treatment in sequence to obtain the epoxy resin for new energy vehicle adhesive.
3. The method for preparing epoxy resin for new energy vehicle glue according to claim 2, characterized in that The Lewis acid used in the etherification reaction process is BF3·Et2O, SnCl4 or AlCl3.
4. The method for preparing epoxy resin for new energy vehicle glue according to claim 2, characterized in that: The etherification reaction is as follows: spirocyclic glycol and toluene are added to a reaction vessel in sequence, the temperature is raised to 80-95°C, the pressure is -0.09MPa, reflux dehydration is carried out until the water content in the system is 0-0.05%, and reflux is stopped. At this time, nitrogen is filled into the system, and Lewis acid accounting for 50-80% of the total mass of Lewis acid is added under a nitrogen atmosphere, the speed is controlled to be 150-200rpm, and the dropwise addition speed is controlled to be 0.85-1.04g / min under stirring conditions. Epichlorohydrin is uniformly added dropwise to the system, and the temperature is kept for 1.5-2.5h after the dropwise addition is completed, and then the remaining amount of Lewis acid is added, and the temperature is controlled to be 85-87°C for etherification reaction for 1-2h to obtain reaction solution I; In the above etherification reaction process, the amount of spirodiol, toluene, Lewis acid catalyst and epichlorohydrin is 1:0.5700-0.6400:0.0010-0.0036:0.6700-0.8200 according to the mass ratio of spirodiol:toluene:catalyst:epichlorohydrin; The closed-loop reaction: under the conditions of controlling the pressure of the reaction liquid I obtained by the etherification reaction to be -0.09 MPa and the temperature to be 60-75° C., controlling the dropping rate to be 0.96-1.05 g / min, adding a 48.5% by mass concentration NaOH aqueous solution to the reaction liquid I, reflux dehydration during the dropping process, and keeping warm for 2-5 hours after the dropping is completed, continuing to maintain the reflux dehydration under negative pressure during the insulation process, and then introducing nitrogen to restore the pressure from negative pressure to normal pressure to obtain a reaction liquid II; In the above-mentioned ring-closing reaction, the amount of the NaOH aqueous solution with a mass percentage concentration of 48.5% is calculated on a molar ratio of spirodiol to sodium hydroxide in the NaOH aqueous solution with a mass percentage concentration of 48.5% relative to the spirodiol used in the etherification reaction process to prepare the reaction solution I, and the molar ratio is 1:2.1-2.3; The refining reaction: the reaction solution II obtained by the ring-closing reaction is placed under an inert gas atmosphere, the temperature is controlled at 75-85° C., a phase transfer catalyst and a 32% by mass concentration NaOH aqueous solution are added in sequence, and the refining reaction is carried out for 2-4 hours to obtain a crude product; In the above-mentioned purification reaction process, the amount of the phase transfer catalyst and the 32% by mass concentration of the NaOH aqueous solution relative to the spirodiol used to prepare the reaction solution I is based on the mass ratio of spirodiol: 32% by mass concentration of the NaOH aqueous solution: phase transfer catalyst of 1:0.087:0.0006; The post-treatment: washing and filtering the crude product obtained from the refining reaction to remove impurities, and then controlling the pressure to -0.9Mpa and the temperature to 120°C for vacuum drying to obtain the epoxy resin for new energy vehicle glue; The washing in the above-mentioned post-treatment process, i.e., in the crude product obtained in the refining reaction, firstly, distilled water in an amount of 0.8-1.2 times the volume of the crude product is added to dissolve sodium chloride, the phase separation is allowed to stand to remove the water phase, and then the product is washed with distilled water for 3 times, and then the residual sodium hydroxide is neutralized with a 5% by volume phosphoric acid aqueous solution before the second washing, and the pH value of the system is adjusted to 7; During the post-treatment process, 500-mesh diatomaceous earth was used for filtration and the pressure was controlled at -0.9 MPa and the temperature was 70-85°C.
5. The method for preparing epoxy resin for new energy vehicle glue according to claim 4, characterized in that: During the etherification reaction, the amount of spirodiol and Lewis acid catalyst used is 1:0.0018 according to the mass ratio of spirodiol to catalyst.
6. An epoxy resin composition, characterized in that The raw materials used for its preparation include the epoxy resin for new energy vehicle glue as claimed in claim 1.
7. The epoxy resin composition according to claim 6, characterized in that The composition and amount of raw materials used in its preparation are calculated by mass as follows:
8. The epoxy resin composition according to claim 7, characterized in that The composition and amount of raw materials used in its preparation are calculated by mass as follows:
9. The epoxy resin composition according to claim 8, characterized in that: The closed toughening agent is Lepro FM 9504, LeproFM 9506, Lepro FM 9508, DY965 or QR-9466 produced by Complex High-tech Materials (Shanghai) Co., Ltd. The curing agent is a dicyandiamide curing agent, and the dicyandiamide curing agent is dicyandiamide; The accelerator is an organic urea accelerator, and the organic urea accelerator is UR 500.
10. The method for preparing the epoxy resin composition according to any one of claims 7 to 9, characterized in that: Add epoxy resin for new energy vehicle glue, 4,8-tricyclo[5.2.1.O(2,6)]decanedimethanol diglycidyl ether epoxy resin, closed toughening agent, curing agent and accelerator into the container in sequence, and then control the rotation speed to 2000-3000rpm for homogeneous mixing to obtain an epoxy resin composition.
11. Use of the epoxy resin composition according to any one of claims 6 to 9 as a structural adhesive for aluminum vehicle bodies.
12. Use of the epoxy resin composition according to claim 11 as an aluminum body automotive structural adhesive, characterized in that The coating thickness of the epoxy resin composition is controlled to be 0.30-0.40 mm. After coating, the temperature is controlled to be 110° C. for curing for 1 hour and 150° C. for curing for 1 hour.